OsCYP706C2 diverts rice strigolactone biosynthesis to a noncanonical pathway branch - Li, Changsheng; Haider, Imran; Wang, Jian You; Quinodoz, Pierre; Duran, Hernando G. Suarez; Méndez, Lucía Reyes; Horber, Robin; Fiorilli, Valentina; Votta, Cristina; Lanfranco, Luisa; de Lemos, Samara M. Correia [UNESP]; Jouffroy, Lucile; et al. (American Association for the Advancement of Science (AAAS), 2024)
Strigolactones exhibit dual functionality as regulators of plant architecture and signaling molecules in the rhizosphere. The important model crop rice exudes a blend of different strigolactones from its roots. Here, we identify the inaugural noncanonical strigolactone, 4-oxo- methyl carlactonoate (4-oxo- MeCLA), in rice root exudate. Comprehensive, cross-species coexpression analysis allowed us to identify a cytochrome P450, OsCYP706C2, and two methyl transferases as candidate enzymes for this noncanonical rice strigolactone biosynthetic pathway. Heterologous expression in yeast and Nicotiana benthamiana indeed demonstrated the role of these enzymes in the biosynthesis of 4-oxo- MeCLA, which, expectedly, is derived from carlactone as substrate. The oscyp706c2 mutants do not exhibit a tillering phenotype but do have delayed mycorrhizal colonization and altered root phenotype. This work sheds light onto the intricate complexity of strigolactone biosynthesis in rice and delineates its role in symbiosis and development.